Modulation of Intestinal Epithelial Cell Proliferation, Migration, and Differentiation In Vitro by Astragalus Polysaccharides - Zhang, Chun Li (Public Library of Science, 2014)
Previous studies have shown that Astragalus polysaccharides (APS) can be used to treat general gastrointestinal disturbances including intestinal mucosal injury. However, the mechanism by which APS mediate this effect is unclear. In the present study, the effects of APS on proliferation, migration, and differentiation of intestinal epithelial cells (IEC-6) were assessed using an in vitro wounding model and colorimetric thiazolyl blue (MTT) assays. The effect of APS on IEC-6 cell differentiation was observed using a light microscope and scanning electron microscope, and the expression of differentiation-specific markers of IEC-6 cells, such as cytokeratin 18 (CK18), alkaline phosphatase (ALP), tight junction protein ZO-2, and sucrase-isomaltase (SI), was determined by immunofluorescence assay (IFA) and real-time PCR. In addition, APS-induced signaling pathways in IEC-6 cells were characterized. Our results indicated that APS significantly enhance migration and proliferation of IEC-6 cells in vitro. APS-treated IEC-6 cells have numerous microvilli on their apical surface and also highly express CK18, ALP, ZO-2, and SI. Moreover, APS-treated IEC-6 cells, in which the activity and expression level of ornithine decarboxylase (ODC) were significantly elevated, also exhibited an increase in cellular putrescine, whereas no significant increase in TGF-β levels was observed. These findings suggest that APS may enhance intestinal epithelial cell proliferation, migration, and differentiation in vitro by stimulating ODC gene expression and activity and putrescine production, independent of TGF-β. Exogenous administration of APS may provide a new approach for modulating intestinal epithelial wound restitution in vivo.